Electroacupuncture Reduces Cerebral Hemorrhage Injury in Rats by Improving Cerebral Iron Metabolism - Qiuxin Chen; Wenjing Song; Yihe Tang; Yizhou Tang; Yuying Kang; Luwen Zhu (Hindawi Limited, 2022)
Objective. To study the effects of electroacupuncture at Baihui and Dazhui points on the expression of hepcidin (Hepc), transferrin (Tf), transferrin receptor (TfR), and ferritin (Ft) in rats with cerebral hemorrhage to provide a theoretical basis for the treatment of cerebral hemorrhage with acupuncture. Method. The model of cerebral hemorrhage in rats was established by autologous blood injection method and treated by electroacupuncture (EA) at the acupoints of Baihui and Dazhui. Hepc siRNA was injected into the lateral ventricle 30 min before model preparation to produce the cerebral hemorrhage model. The modified neurological severity score (mNSS) was used to assess the neurological function, and the total iron content in brain tissue was determined using atomic absorption spectrometry; the expression of Hepc, Ft, Tf, and TfR in perihematoma tissue was detected using immunohistochemistry; the interference efficiency of Hepc siRNA was detected using western blot and reverse transcription polymerase chain reaction (RT-PCR). Results. The degree of neurological deficit showed a downward trend at 3 days, 7 days, and 14 days, and electroacupuncture significantly reduced the neurological deficit score at each time point (P<0.01). Regarding total iron content in brain tissue, on the 3rd day, the 7th day, and the 14th day, the iron content of the hematoma tissue after intracerebral hemorrhage was reduced by electroacupuncture (P<0.01). Regarding immunohistochemical results. Hepc, Ft, Tf, and TfR protein expressions on day 14 were significantly higher after cerebral hemorrhage (P<0.01). After electroacupuncture, the expression of Hepc, Ft, Tf, and TfR protein was significantly reduced (P<0.01). Western blot and RT-PCR revealed that the interference efficiency of Hepc siRNA was statistically significant (P<0.01). Conclusion. Electroacupuncture can reduce neurological severity scores in rats with cerebral hemorrhage and may exert cerebral protective effects by reducing Hepc protein and gene expression; lowering Ft, Tf, and TfR protein expression; and promoting iron metabolism in the brain of rats with cerebral hemorrhage.